Athanasius' ‘Vita Antonii’ as Political Theology: The Call of Heavenly Citizenship - Cartwright, Sophie (The journal of ecclesiastical history, 2016)
This article explores the political theology of Athanasius' ‘Life of Antony’. It argues that the work is profoundly concerned with the relationship between the Church and the empire, which it treats as a component of the relationship between the Church and the fallen world order. Athanasius explores this issue through Antony, striving to live as a citizen of heaven within the fallen world. Athanasius sees allegiance to earthly authority as problematising allegiance to the heavenly kingdom, which is bound up with a concern for the Christian's identity: the Christian must understand himself and the world in relation to the kingdom of heaven, rather than the earthly kingdom.